KARBON AKTIF AMPAS TEBU SEBAGAI ADSORBEN PENURUN KADAR BESI DAN MANGAN LIMBAH AIR ASAM TAMBANG - Azwardi Imani; Tatan Sukwika; Laila Febrina (Jurnal Teknologi, 2021)
Bagasse contains cellulose that can be used as raw material to activated carbon. Acid mine drainage has high levels of iron and manganese so bagasse activated carbon is used as an adsorbent for reducing iron and manganese levels in acid mine drainage. Bagasse was converted into activated carbon by dehydration, carbonization, and activation processes. Then activated carbon was tested for weight quality, optimum contact time, and effectiveness for reducing iron and manganese levels in acid mine drainage. The results of the quality test of activated carbon have met the standards required by SNI No. 06-3730-1995. The optimum weight of activated carbon is 3 grams with a contact time of 60 minutes. Iron content obtained at 4 mg / L with a removal percentage of 79.65% and Manganese content obtained at 4.12 mg / L with a removal percentage of 60.00% in acid mine drainage. The value of Manganese content still does not meet the quality standard set by the Decree of the State Minister for Environment No. 113 of 2003. For future studies can make a higher variation in the weight of activated carbon bagasse.